Evaluation of Frequency Distribution of Dental Complaints According to the Principles of Observing Professional Ethics in Isfahan City between 2010 to 202 - Fahimeh Pakravan; Zohreh Gholam (Isfahan University of Medical Sciences, 2022)
One of the problems and challenges faced in the field of dentistry can be attributed to filing a lawsuit against the dentist resulting indiscontent,consuming time and energy from both parties.This study can be useful for students and dentists because it will enable them to identify cases that lead to filing lawsuits and in turn adhere to the principles of professional ethics when treatingand interacting with patients. The purpose of this study was to investigate the relationship between adherence to the principles of professional ethics and frequency of lawsuits in Isfahan city between2010 to 2020.Materials & Methods:In this Cross-Sectional study, 706 files of lawsuits during 2010-2020 at the Isfahan medical archives of records and the deputy department of treatment were evaluated and the relevant information was extracted. The data were analyzed using descriptive statistics test.Results:A rising trend was observed in the rate of lawsuits. The most common reason for the lawsuits was related to not having the knowledge, skill and experience, additional consultations and referrals to other dentists, overbilling and unethical behavior in the workplace. A higher Frequency of lawsuits were associated to male and general dentists.Conclusion:Dental complaints had a rising trend, and the most commonly reported cases were related to not having the knowledge, skill, experience and additional consultation and referrals